PHYSICAL AND MECHANICAL PROPERTIES OF ORIENTED WOOD-CEMENT BOARDS PRODUCED WITH FIVE EUCALYPTUS SPECIES - Souza da Rosa, Thiago; Rosa Schweitzer, Vinícius; Trianoski, Rosilani; Iwakiri, Setsuo (Floresta, 2017)
This study aimed to manufacture oriented wood-cement boards using five Eucalyptus species and mixture between then, to compare the effect of the particles orientation, and to evaluate the physical and mechanical properties according to competent standards. The species studied were: Eucalyptus benthamii, Eucalyptus dunni, Eucalyptus grandis, Eucalyptus saligna, Eucalyptus urograndis the mixture between them and the Pinus taeda as control. The bonding agent employed was commercial grade Portland cement types CP II-Z-32R. The panels had dimensions of 48 x 48 x 1.2 cm and nominal specific mass of 1.2 g/cm³. The cement/wood/water mass ratio used was 2.5:1:1 and 2% of CaCl2 by weight of cement was used as an additive. The orientation of strands did not influence the dimensional stability properties. All boards had very low IB strength, being that, none treatments reached the requirements to internal bond of competent standards. The MOR and MOE results indicated that species mixture can be obtained boards with properties similar to pure species. In general, the boards showed low mechanical strength what can be attributed to particles geometry and wood-cement ratio. The wood of Eucalyptus species presents potential for use in cement-wood panels.